EFEKTIVITAS BEBERAPA JENIS FUNGI MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN TANAMAN KARET (Hevea brassiliensis Muell. Arg.) DI PEMBIBITAN The effectivity some type Arbuscular Mychorrizal Fungi on rubber (Hevea brassiliensis Muell. Arg.) growth in seedlings - Perdana Roy Oksemsa Purba; Nini Rahmawati; Emmy Harso Kardhinata; Asmarlaili Sahar (Universitas Sumatera Utara, 2014)
The application of chemical fertilizer is often selected by farmer to increase the rubber growth.However the uses of chemical fertilizer in process of time will bit into land fertility caused the deathof microbe in the ground and the land condition will be solid, it caused root plants can not absorb anutrition. So the application of biological fertilizer like AMF expected to replace chemical fertilizerto increase a rubber growth in continuing time. This research had been conducted in plastic house ofthe Agriculture Faculty, University of North Sumatra (± 25 m asl) from July - September 2013.Method of this research is non factorial randomized block design with 7 treatments, that is the typeof AMF spore (big black AMF spores, small black AMF spores, big yellow AMF spores, smallyellow AMF spores, black indigenous of rubber AMF spores, yellow indigenous of rubber AMFspores, spores of Glomus spp.). Parameters observed were addition of plant height, root volume,weight of dry shoot, weight of dry root and total of spores.The result showed that the addition ofsome type AMF significantly influenced total of spores, but for the other parameters influenced notsignificantly.Keywords : arbuscular mychorrizal fungi, rubber